Chalcone‐based derivatives as new scaffolds for hA3 adenosine receptor antagonists. (25th January 2013) - Vazquez‐Rodriguez, Saleta; Matos, Maria João; Santana, Lourdes; Uriarte, Eugenio; Borges, Fernanda; Kachler, Sonja; Klotz, Karl‐Norbert
Abstract Objectives With the aim of finding new adenosine receptor (AR) ligands based on the chalcone scaffold, we report the synthesis of a new series of coumarin–chalcone hybrids and the pharmacological characterization of their actions at four subtypes of AR. Methods The synthesized compounds 5–10 were characterized in radioligand binding (A1, A2A and A3) and adenylyl cyclase activity assays (A2B) to determine the affinity of the compounds for the four human AR (hAR) subtypes. Key findings Coumarin–chalcone hybrids were found to be ligands with a novel structure, not reported thus far, that showed varying affinity and selectivity for AR subtypes. Conclusions The coumarin–chalcone hybrids in which ring B of the chalcone scaffold was a thiophene (compounds 5 and 9) were found to be the most potent compounds of the series. Compound 9, in which ring A of the chalcone moiety was the phenyl ring of the coumarin, showed similar activity against hA1, hA2A and hA3 ARs, while compound 5, in which ring A of the chalcone was substituted by the benzopyrone ring of the coumarin moiety, showed similar activity only at the hA3 AR and, therefore, was deemed to be selective (Ki (dissociation constant) = 5160 nm).